A Virtual Learning Object (VLO) to Promote Reading Strategies in an English for Specific Purposes Environment - Sandra Cecilia Hernández Urrego (HOW)
This study describes the influence of a Virtual Learning Object in the promotion of reading strategies in a class of English for Specific Purposes for the majors of Social Communication and Journalism at a private institution of higher education in Bogota, Colombia. Students’ failure to meet the school standards led to the design and implementation of a virtual tool to support academic achievement. Data came from a sample of 15 students’ reading cycle reports, self-assessment of progress, questionnaires, and interviews. Results suggest that the developed VLO did promote the participants’ appropriation of reading strategies proposed in the design of the course. The process with the VLO not only prompted higher reading comprehension, but also facilitated and enriched learning experiences.